Preserving the Saparan Tradition as a Means of Instilling Character Values in the Young Generation in the Krangkeng Hamlet Community - Erica (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Saparan Tradition is one of the cultural traditions that is still preserved by the people of Dusun Krangkeng. This tradition functions not only as an annual customary ritual but also as a medium for instilling character values in the younger generation. This study aims to describe the forms of preservation of the Saparan Tradition and to identify the character values embedded within it. This research employs a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research subjects included community leaders, traditional leaders, religious leaders, and young people involved in the Saparan Tradition. The results show that the preservation of the Saparan Tradition is carried out through active community involvement in every stage of the activities, from preparation and the main event to the closing ceremony. This tradition embodies strong character values, including harmony, mutual cooperation, religiosity, responsibility, and love for local culture. These values are directly instilled through social practices and the active participation of the younger generation in traditional activities. Thus, the Saparan Tradition plays a strategic role as a means of character education based on local culture, which remains relevant in facing the challenges of modernization. Preserving this tradition is essential to maintaining cultural identity while strengthening the character of the younger generation